2021
DOI: 10.3389/fnins.2021.674204
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Sleep, Circadian Rhythms and Immunity – Repurposing Drugs and Chronotherapeutics for SARS-CoV-2

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has affected nearly 28 million people in the United States and has caused more than five hundred thousand deaths as of February 21, 2021. As the novel coronavirus continues to take its toll in the United States and all across the globe, particularly among the elderly (>65 years), clinicians and translational researchers are taking a closer look at the nexus of sleep, circadian rhythms and immunity that may contribute toward a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 222 publications
(243 reference statements)
0
10
0
1
Order By: Relevance
“…Since circadian rhythms observed in the immune system might not only affect the immune response as presented by the titers of antibodies [ 45 ], but also the strength and occurrence of immediate and late ADR [ 46 ], we asked whether number and characteristics of the reported ADR correlate with time-of-day of vaccination. So far, Langlois et al [ 26 ] and Pollmann and Pollmann [ 24 ] have presented that local ADR tend to be more frequent in individuals revaccinated late during the daytime.…”
Section: Discussionmentioning
confidence: 99%
“…Since circadian rhythms observed in the immune system might not only affect the immune response as presented by the titers of antibodies [ 45 ], but also the strength and occurrence of immediate and late ADR [ 46 ], we asked whether number and characteristics of the reported ADR correlate with time-of-day of vaccination. So far, Langlois et al [ 26 ] and Pollmann and Pollmann [ 24 ] have presented that local ADR tend to be more frequent in individuals revaccinated late during the daytime.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the shape of the association changed (from reverse J-shape to linear) with age, but morning vaccination was the most potent in mounting antibody titers across all age groups. The age-specific results might be explained by a cross-talk of aging of the circadian system and sleep homeostasis (Giri et al, 2021) with age-related declines in immunity such as impaired immune cell function, diminished chemokine production, that may lead to reduced antibody response following vaccination or infection (Bartleson et al, 2021; Blomberg and Frasca, 2013). We also found suggestive evidence of effect modification by sex, with morning vaccination (vs early afternoon) stimulating a stronger vaccine response among male participants, although our stratified analyses were of limited power.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian rhythms regulate the immune system by a temporal modulation of the immune function (Giri et al, 2021; Sengupta et al, 2021), with human immune cell counts and inflammatory markers showing daytime variation (Wyse et al, 2021). Circadian parameters such as the time of day of vaccine administration may influence vaccine-induced immune response.…”
mentioning
confidence: 99%
“…It is known that cholesterol production in the body peaks at night [ 30 ]. A recent study reported that statin drugs that decrease cholesterol biosynthesis by inhibiting HMGCoA reductase minimize the severe side effects of COVID-19 [ 31 ]. As a result of this study, it was observed that nighttime administration of the same dose of statins significantly reduced cholesterol levels in COVID-19 patients compared to the morning test group.…”
Section: Melatonin and Importance Of Circadian Rhythm In Covid-19mentioning
confidence: 99%